Impact of the COVID-19 pandemic on sports and exercise - Wong, A. Y.-Y.; Ling, S. K.-K.; Louie, L. H.-T.; Law, G. Y.-K.; So, R. C.-H.; Lee, D. C.-W.; Yau, F. C.-F.; Yung, P. S.-H. (Asia Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2020)
Background: COVID-19 is a droplet-transmitted potentially fatal coronavirus pandemic affecting the world in 2020. The WHO recommended social distancing and human-to-human contact was discouraged to control the transmission. It has put many countries in a state of lockdown and sporting events (including the 2020 Olympics) have been affected. Participation in sports and exercise, typically regarded as healthy activities, were also debated. The local professional football leagues, governed by the Hong Kong Football Association, ultimately postponed all matches after much deliberation on the transmission risk for the spectators and on-field players. Large spectating crowds are well-known to be infectious hazards, but the infection risk for on-field players is less recognized. Aside from watching professionals exercise, many people opted to hike in the countryside during the weekends to avoid city crowds. This led to a widespread discussion on the issue of wearing a facemask during outdoor activities.